Research on residents’ intention to settle and the mediating effect of green policy leadership - Hiroko Oe; Yasuyuki Yamaoka; Sitsada Sartamorn (Health Economics and Management Review)
This research constitutes a comprehensive exploration aimed at disentangling the intricate web of relationships between citizens’ interest and their proclivity to engage with policies instituted by local governments, and the consequential impact on their intent to settle in a specific geographical area. Employing a robust quantitative analysis, the authors embarked on a mission to decipher the multifaceted interplay between citizens’ attitudes, local policies, and their desire to establish roots in a particular locale. To facilitate this exploration, the authors meticulously devised a sophisticated model, wherein “welfare and health promotion” and “social participation and exchange” emerged as the primary latent factors, while “green policy leadership” took center stage as the mediating force in the analytical framework. The research design involved a meticulous examination of the paths leading to citizens’ “settlement intention”. Drawing insights from the outcomes of an extensive intention survey, the authors meticulously collected and cleaned a rich dataset sourced from citizen surveys conducted in City A, strategically nestled in the heart of Japan’s Honshu island. This dataset, after a stringent filtering process, crystallised into a substantial sample size of 466 responses. The study’s outcomes reveal a nuanced narrative regarding the relationship between social participation and exchange policies and citizens’ intent to settle. Intriguingly, the findings suggest that these policies, when considered in isolation, may not exert a direct influence on citizens’ proclivity to settle in a municipality. However, their potency becomes evident when channeled through the lens of green policy leadership. This signifies the importance of local governments adopting a holistic approach that not only emphasises individual policies but also recognises the synergistic impact achieved through the integration of green policy leadership. Furthermore, the research extends beyond the conventional examination of policies by delving into the unexplored realms of proactive appeals and communication methods employed by local governments. Going beyond the traditional purview of green policy, the study illuminates the critical role played by effective communication strategies. It suggests that a proactive approach in communicating policies, coupled with a leadership stance that accentuates green policies, serves as a catalyst for aligning local residents’ instructions with municipal policies. This dynamic interplay fosters a positive environment that, in turn, augments citizens’ willingness to settle in the area.